Pola Relasi Eksekutif Dan Legislatif Pada Penyusunan Legislasi Daerah - Wance, Marno; Suranto, Suranto (Journal of Governance and Public Policy, 2017)
This study is shown to measure the impact of the rising of many South Buru district budget is problematic(mistimed), namely from the year 2010 to 2015 discussions always happen tug of interests that result in a delayof APBD. therefore be important to do a study on (1), the Executive and Legislative Relationship Patterns inSouth Buru budget discussion. (2) Factors relations executive and legislative In the discussion of the budget.based on the findings of this study concluded that the first, found three patterns of interaction (accommodation,domination, compromise), but between the three patterns of interaction of the budget policy discussion found anymore process dominate. Second, the interaction patterns decisional is a pattern of disagreement that took placein the formulation (KUA) and (PPAS) resulting keterlamabatan determination of the budget, the interactionpatterns of power that occurred bargaining (barganing) to exchange the interest of the legislature to theexecutive are not accommodated On (RKA) SKPD These three, namely the interaction patterns AnticipatedReaction South Buru District Government receives the benefit of parliament who form the recess recommendationto maintain the stability of the Year 2015.Keempat discussion of budget, non-decisional interaction pattern thatthe legislature refuses to KUA and PPAS discussion because of the executive did not submit documents PlansWork Budget (RKA) from each SKPD. While facto factors influencing ang Relationship Patterns executive andlegislative discussion of budget 2015 ie Personal Bachground, political Bachground